The Existence of Islamic Education in the National Education System in Indonesia - M. Rofi Fauzi; Ahmad Safi'i (Yayasan Zia Salsabila, 2023)
Islamic education as a formal teaching material in Indonesia has experienced at least three phases, namely the first phase since the entry of Islam into Indonesia until the era of Islamic education reform in Indonesia, the second since the emergence of ideas for Islamic education reform, and the third since the creation of the National Education System Law (in 1989). This research aims to analyze the existence of Islamic education in the national education system in Indonesia. This type of research uses a qualitative approach with a literature study method. Data sources are quoted from credible pages such as Google Scholar and SINTA. Next, the data was analyzed and checked for validity through data triangulation. The results of this research conclude that Islamic education is recognized for its existence in the national education system, which is divided into three things. First, Islamic education as an institution, second, Islamic education as a subject, and third, Islamic education as a value.